Pemberdayaan Masyarakat Melalui Agroindustri Ikan Air Tawar Waduk Batu Bulan Di Desa Maman - Rudi Masniadi; Jhon Kenedi; Yudiaihdiansyah Yudiaihdiansyah (Universitas Mataram, 2020)
Batu Bulan Reservoir, located in Maman Village, Moyo Hulu Subdistrict, Sumbawa Regency, is the longest dam in NTB Province which has high potential for developement. One example is the abundance of fishermen's catches. Furtehermore, the abundant catches result in fish is sold in significantly low prices. Hence, the income of said fishermen in this area is particularly low. It happens due to those fishermen do not have any other option considering their lack of knowledge and skills in processing and preserving their catches for a longer time in order to increase their market value. As far as increasing market value is corncerned, freshly caught fish hold small price in the market for it is raw. If it goes through industrial processes and is transformed into a product of processed fish (agroindustry), of course its market value will rise that in turn will automatically affect its price, consequently will increase the income of the family of fishermen in Maman. The objective of this action is to equip the fishermen in Maman with the necessary skills and knowledge to process their own catches industrially so that it will increase in value and strengthen the local economy. Using the method of training and accompaniment, this activity targets 30 people, which are housewives of fishermen in Maman. The outcome of this program can be assessed with observing the increasing of people of Maman to process fish by 80%. Moreover, two products from this program which are Abon Ikan (Shredded Fish) and Stick Tulang Ikan (Fish Bone Stick) can be realized.